Morphology and composition of Zn–Ni alloy obtained from sulphate bath containing complexing agent. (3rd May 2020) - Faid, H.; Galvan, J. C.
ABSTRACT: Zn–Ni alloys were electrodeposited on stainless steel from a sulphate bath in the presence of EDTA (ethylenediaminetetraacetic acid) as a complexing agent. The electrochemical behaviour of the bath was studied by cyclic voltammetry (CV), chronoamperometry (CA). Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis showed a change in surface morphology; the phase structure corresponds to the face centre cubic (fcc) structure attributed to the γ phase (Ni5 Zn21 ). The corrosion measurements of the obtained deposits with various EDTA concentrations were studied using potentiodynamic polarisation. Results showed that the deposit obtained in the presence of a low EDTA concentration (0.25 g L −1 ) exhibits better corrosion resistance.